Descending thoracic aorta dissection associated with esophageal carcinoma - Kaushik Saha; Debabrata Saha; Ankan Bandyopadhyay; Debraj Jash (South Asian Journal of Cancer, 2013)
The association of aortic dissection with a malignancy is a rare finding and previous reports are usually those of primary aortic sarcomas. A 45-year-old male presented to us with chest pain and dysphagia for 1 month with a background history of obstructive airway disease and uncontrolled hypertension. In this report we present a case of typical descending aorta dissection with associated esophageal carcinoma.